Reductions in neuronal and glial density characterize the dorsolateral prefrontal cortex in bipolar disorder - Rajkowska, Grazyna; Halaris, Angelos; Selemon, Lynn D (Biological psychiatry (1969), 2001)
Background: Bipolar disorder (BPD) is a mental illness in which depression and mania typically alternate, and both phases can present with psychotic features. The symptomatology of BPD, therefore, resembles major depressive disorder (MDD) and schizophrenia (SCHZ), posing diagnostic dilemmas. Distinct alterations in cellular architecture of the dorsolateral prefrontal cortex distinguish SCHZ and MDD, whereas the cellular neuropathology of BPD has not been studied. Methods: Dorsolateral prefrontal area 9 was analyzed using a three-dimensional morphometric method in postmortem brains from 10 BPD patients and 11 matched nonpsychiatric control subjects. Results: Area 9 in BPD was characterized by reduced neuronal density in layer III (16%–22%) and reduced pyramidal cell density in layers III and V (17%–30%). A 19% reduction in glial density was found in sublayer IIIc coupled with enlargement and changes in shape of glial nuclei spanning multiple layers. Conclusions: The morphologic signature of BPD, i.e., decreased neuronal and glial density in association with glial hypertrophy, is distinct from previously described elevations in neuronal density in SCHZ, instead resembling the reductions in cell density found in MDD. Thus, the neuropathologic distinctions between BPD and SCHZ are indicative of separate mental illnesses, each with a unique morphologic disturbance of specific neural circuits.